Evaluation of coefficients to derive organ and effective doses from cone-beam CT (CBCT) scans: a Monte Carlo study. (22nd January 2018) - Abuhaimed, Abdullah; Martin, Colin J
Abstract: Regular imaging is used throughout image guided radiation therapy to improve treatment delivery. In order for treatment procedures to be optimized, the doses delivered by imaging exposures should be taken into account. CT dosimetry methods based on the CT dose index (CTDI), measured with a 100 mm long pencil ionization chamber (CTDI100 ) in standard phantoms, are not designed for cone-beam CT (CBCT) imaging systems used in radiotherapy, therefore a modified version has been proposed for CBCT by the International Electrotechnical Commission (CTDIIEC ). Monte Carlo simulations based on a Varian On-Board Imaging system were used to derive conversion coefficients that enable organ doses for ICRP reference phantoms to be determined from the CTDIIEC for different scan protocols and different beam widths (80–320) mm. A dose–width product calculated by multiplying the CTDIIEC by the width of the CBCT beam is proposed as a quantity that can be used for estimating effective dose. The variation in coefficients with CBCT beam width was studied. Coefficients to allow estimation of effective doses were derived, namely 0.0034 mSv (mGy cm) −1 for the head, 0.0252 mSv (mGy cm) −1 for the thorax, 0.0216 mSv (mGy cm) −1 for the abdomen and 0.0150 mSv (mGy cm) −1 for the pelvis, and these may be applicable more generally to other CBCT systems in radiotherapy. If data on effective doses are available, these can be used in making judgements on the contributions to patient dose from imaging, and thereby assist in optimization of the treatment regimes. The coefficients can also be employed in converting dosimetry data recorded in patient records into quantities relating directly to patient doses.